China's capacity of hospitals to deal with infectious diseases in the context of climate change. (June 2018) - Tong, Michael Xiaoliang; Hansen, Alana; Hanson-Easey, Scott; Xiang, Jianjun; Cameron, Scott; Liu, Qiyong; Liu, Xiaobo; Sun, Yehuan; Weinstein, Philip; Han, Gil-Soo; Bi, Peng
Abstract: Objectives: Infectious diseases are a major cause of morbidity and mortality in China. The capacity of hospitals to deal with the challenge from emerging and re-emerging infectious diseases due to climate change is of great importance to population health. This study aimed to explore the capacity of hospitals in China to deal with such challenges. Methods: A cross-sectional questionnaire survey was utilized to gauge information regarding capacity of hospitals to deal with infectious diseases in the context of climate change among 611 clinical professionals whose roles pertained to infectious disease diagnosis, treatment and management in Anhui Province of China. Descriptive analysis and logistic regression analysis were performed on the data. Results: More than 90% of participants believed climate change would have an adverse influence on population health and infectious disease control in China. Most indicated that their hospitals were well prepared for emerging infectious diseases at present, and they considered that logistical support in hospitals (e.g. administrative and maintenance services) should be strengthened for future capacity building. The majority of participants suggested that effective prevention and control measures, more interdisciplinary collaborations, more funding in rural areas for health care, and improved access to facilities enabling online reporting of infectious diseases, were extremely important strategies in building capacity to curb the population health impact of emerging and re-emerging infectious diseases due to climate change in China. Conclusions: Clinical professionals recognized that climate change will likely increase the transmission of infectious diseases. Although rural health care and hospitals' logistical support need to be improved, most professionals believed their hospitals to be capable of dealing with emerging diseases. They thought that interdisciplinary and cross-regional collaborations, together with necessary resource support (e.g. improved facilities for rural health care) would be important control strategies. Highlights: Most participants indicated climate change would affect infectious diseases. Generally, hospitals were well prepared for emerging infectious diseases. Hospital's logistical support should be strengthened urgently. Improving the capacity of rural health care and hospitals were extremely important.